Phytochemical and Safety Evaluations of Volatile Terpenoids from Zingiber cassumunar Roxb. on Mature Carp Peripheral Blood Mononuclear Cells and Embryonic Zebrafish - Raktham Mektrirat; Terdsak Yano; Siriporn Okonogi; Wasan Katip; Surachai Pikulkaew (Molecules, 2020)
Pharmaceutical products of essential oil from Zingiber cassumunar Roxb. are extensively being developed, while the research on their safety is seldom documented. The aim of the present study was to evaluate the phytochemical profile and the effect of cassumunar ginger oil on cell-based assay and the zebrafish model. The essential oil was isolated from fresh rhizomes of Z. cassumunar using simultaneous steam-distillation. Chemical composition was analyzed using gas chromatograph coupled to a mass spectrometer (GC-MS). Effect of cassumunar ginger oil on adult carp fish peripheral blood mononuclear cells (PBMCs) was investigated using MTT assay. The embryotoxic and teratogenic effects of cassumunar ginger oil were studied in zebrafish embryos. GC-MS results showed that the essential oil was composed of sabinene (43.54%) and terpinen-4-ol (29.52%) as the major phytoconstituents. No fish PBMC cytotoxic effect was observed with the concentration less than 50 µg/mL of cassumunar ginger oil. Our results showed for the first time the embryotoxic and teratogenic effects of cassumunar ginger oil in zebrafish embryos. The result indicated that the cassumunar ginger oil induced zebrafish embryotoxicity in a concentration-dependent manner. At 500 µg/mL of cassumunar ginger oil demonstrated significantly moderated embryotoxicity within 24 h (p < 0.05). The survival rate of 100 µg/mL of cassumunar ginger group was markedly declined to zero at 96-h post-fertilization (log-rank test, p = 0.001). However, survival rates of zebrafish embryo in the 1 and 10 µg/mL cassumunar ginger groups were more than 90% throughout the trial period. Moreover, very low teratogenicity to the zebrafish embryo was also observed in 1 and 10 µg/mL of cassumunar ginger groups. Our findings suggest that there is hardly any cytotoxicity, embryotoxicity and teratogenicity at concentrations less than 10 µg/mL of cassumunar ginger oil. However, the toxicity assessment of its pharmaceutical product should prove for further consumer protection.